Therapeutic Effect of Xuebijing, a Traditional Chinese Medicine Injection, on Rheumatoid Arthritis - Li, Shutong (Evid Based Complement Alternat Med, 2020)
BACKGROUND: Traditional Chinese medicine considers that rheumatoid arthritis (RA) is caused by blood stasis, heat, and toxins. Xuebijing (XBJ), a traditional Chinese medicine compound injection, activates blood circulation to dissipate blood stasis, eliminating pathogenic heat from the blood and degrading toxins. XBJ was approved by the China FDA to treat for many years. This study examined the potential therapeutic effects of XBJ on RA and rat collagen-induced arthritis (CIA). METHODS: XBJ was cultured with the synovial fluid (SF) of RA patients. XBJ was also injected into CIA rats. Changes in Treg and Th17 cell levels in the peripheral blood (PB), SF, and spleen and changes in Th1/Th2 and cytokine levels in PB were detected using flow cytometry. Four RA patients were treated using XBJ based on Chinese medical theory and Chinese medicine indications. RESULTS: Following culture with XBJ, the proportion of Treg cells (P=0.007) was significantly increased in RA SF, while the Th1/Th2 ratio remained unchanged. After XBJ treatment, CIA in rats was significantly relieved (P=0.007) was significantly increased in RA SF, while the Th1/Th2 ratio remained unchanged. After XBJ treatment, CIA in rats was significantly relieved (β, IL-6, IL-17A, IFN-γ, and TNF-α decreased (P=0.007) was significantly increased in RA SF, while the Th1/Th2 ratio remained unchanged. After XBJ treatment, CIA in rats was significantly relieved (P=0.007) was significantly increased in RA SF, while the Th1/Th2 ratio remained unchanged. After XBJ treatment, CIA in rats was significantly relieved (P=0.007) was significantly increased in RA SF, while the Th1/Th2 ratio remained unchanged. After XBJ treatment, CIA in rats was significantly relieved (P=0.007) was significantly increased in RA SF, while the Th1/Th2 ratio remained unchanged. After XBJ treatment, CIA in rats was significantly relieved (P=0.007) was significantly increased in RA SF, while the Th1/Th2 ratio remained unchanged. After XBJ treatment, CIA in rats was significantly relieved ( CONCLUSION: XBJ can restore the immune balance to treat RA and CIA. Therefore, XBJ could be a potential therapeutic drug for RA.